Frequency Of Depression In Patients With Vitamin B12 Deficiency - Anam Fatima; Faridullah Shah; Hareema Saeed Khan; Kashif Rauf; Safdar Ali; Shahid Ali Khan (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of depression in patients with vitamin B12 deficiency.